"CORRELATION BETWEEN PH, CONCENTRATION OF CA2+, p3+, NA+ AND K+ OF SALIVA AND DMVF INDEX IN 118 DENTISTRY STUDENTS OF TEHRAN UNIVERSITY OF MEDICAL SCIENCES " - Sh. Jafari; D. Sedghi (Tehran University of Medical Sciences, 2000)
118 Dentistry students were studied to show the possible correlation between pH, concentration of Ca2+, P3+, Na+, and K+ of saliva and Decay, Missing, and Filling Tooth (DMFT index). Candidates were between 20 and 30 years old and had no background systemic disorders; medial and dental histories, age, sex, and DMFT index were recorded in a questionnaire organized for this purpose. Saliva samples were collected according to the unstimulated whole saliva method. Saliva was expectorated into the test tubes and the PH, Ca2+, p3+, Na+, and K+ measured. Results from case and control groups were compared and statistically analyzed. It was concluded that there was no meaningful correlation between pH, concentration of Ca2+, P3+, Na+, and K+ and dental decay in the population, where as in men there was a meaningful association between pH and decay. Also in women alone there was a relative correlation between concentration of P3+ and decay (PV=0.06).